Intercultural communication in German-Dutch business contexts (Volume 58) - Thesing, Christopher (2016)
Germany and the Netherlands maintain close relationships. Over the last few decades their relations have constantly intensified, resulting in today's close cooperation, consultations and interrelations in a variety of fields. However, despite their close ties and geographic proximity there are cultural differences between the two countries that lead to disturbances in cross-border cooperation. These cultural differences manifest in behavior, perceptions and attitudes and can lead to irritations, problems and even conflicts in German-Dutch interaction. This book provides an analysis of cultural characteristics that play a role in German-Dutch interaction as well as their relevance and conflict potential. With an entanglement of different methods both the rather concrete and visible manifestations and the general, rather superordinate and underlying aspects of culture are analyzed, providing the readers with a comprehensive understanding of their neighboring culture and enabling them to avoid irritations and conflicts when dealing with Dutch or Germans.